THE BEST INNOVATION OF DEVELOPMENT IN MECHANICAL ENGINEERING - Abdashimova Munisa; Jabborxonova Gulzodaxon (Лучшие интеллектуальные исследования, 2023)
Abstract. The applications of machine learning and artificial intelligence systems in CNC machine tools are examined in this study by analyzing recent achievements from published papers. The main aim of this study is to provide an overview of current studies on machine learning and artificial intelligence techniques in CNC machining operations in order to provide a useful study for the researchers in the interesting field.